Habitat characteristics of breeding Eurasian Whimbrel Numenius phaeopus on Mainland Shetland, Scotland, UK. Issue 4 (1st October 2016) - Massey, Kate; Cosgrove, Peter; Massey, Fergus; Jackson, Digger; Chapman, Mark
ABSTRACT: Capsule: Habitats used by Whimbrel Numenius phaeopus chicks for feeding are significantly different to those used by adults for feeding and nesting. Aim: To identify habitats used by breeding Whimbrel on Mainland Shetland. Methods: Fourteen study sites were used to identify three main components of Whimbrel breeding habitats: (i) adult territorial and foraging habitats; (ii) nest site habitats; (iii) chick feeding habitats. The relationship between these components was investigated using principal components analysis. Results: Habitats used by adults comprised blanket bog dominated by ling heather, cross-leaved heath, common cottongrass, hare's-tail cottongrass, deergrass and purple moor-grass. There was a thick layer of bryophytes but few forbs. Habitat used for nesting was similar to the general habitat used by adults. The habitats in which Whimbrel chicks foraged were significantly different in structure from the habitats used by adults. The chick feeding areas were characterized by small, wet and often linear features. Conclusion: Habitat requirements by Whimbrel chicks for foraging differed from those of adult Whimbrel for nesting. Habitat structure is important for chicks and the presence of small, wet linear features may be a limiting component on otherwise apparently suitable adult Whimbrel habitats.